(3TQM bUjOI HGfJ SYGOs - (3eLghds; (3RgjQ Hf CHj Sdej , RgjQ Hf CHj Sdej Hf QHjYI Hf QjGM Hf bQI Hf GdMGQK GdeRfj GdeVQjs ((3YHO Gddg Hf YHO GdhGMO HGTf CYjGf GdYHO GdSdGe s)
(3ChdgG (B:s
(3HGfJ SYGO abdHi Gdjhe eHJhd hcCf ai bUQ ef YgOgG Whd jbhd hEf cGf YgOfG HgG MOjKkG bUjQkG aEfg Whjd YdjfG s
(3BNQgG (B:s
(3JYH ajg JTQH jbGd YH GdeGA jYHg YHG faGNjf efNQjf CVQhfG efg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B26s
(3HgG Jedc HGSe YHO Gddg Hf YHO GdhGMO Hf YHO GddWja Hf TYjH Hf YHO GdSdGe hjQLY JGQjNgG Edi SfI (B1294 (3g`s
(3hQO ai cTa GdXfhf ai L(B2 (3U` (B1329 (3Cf bUjOI HGfJ SYGO gi deDdagG cYH Hf RgjQs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdeLGejYs